2018
DOI: 10.1111/bjh.15384
|View full text |Cite
|
Sign up to set email alerts
|

Elotuzumab monotherapy in patients with smouldering multiple myeloma: a phase 2 study

Abstract: Summary Smouldering multiple myeloma (SMM) is associated with increased risk of progression to multiple myeloma within 2 years, with no approved treatments. Elotuzumab has been shown to promote natural killer (NK) cell stimulation and antibody-dependent cellular cytotoxicity (ADCC) in vitro. CD56dim (CD56dim/CD16+/CD3−/CD45+) NK cells represent the primary subset responsible for elotuzumab-induced ADCC. In this phase II, non-randomized study (NCT01441973), patients with SMM received elotuzumab 20 mg/kg intrave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…10 Strategies using other immunotherapeutics, such as vaccines (PVX-410), elotuzumab, and daratumumab, have reported ORR of 0%, 10%, and 56% and CR rate of 0%, 0% and 5%, respectively. [28][29][30] Emerging data from the use of myeloma-like regimens, such as carfilzomib, lenalidomide, and dexamethasone with or without autologous stem cell transplantation, have reported high ORR of 98% and 100%, and MRD-negative CR of 55% and 63%, respectively. 31,32 However, it is unclear at this time whether the morbidity associated with such intensive therapies is justified for SMM.…”
Section: Discussionmentioning
confidence: 99%
“…10 Strategies using other immunotherapeutics, such as vaccines (PVX-410), elotuzumab, and daratumumab, have reported ORR of 0%, 10%, and 56% and CR rate of 0%, 0% and 5%, respectively. [28][29][30] Emerging data from the use of myeloma-like regimens, such as carfilzomib, lenalidomide, and dexamethasone with or without autologous stem cell transplantation, have reported high ORR of 98% and 100%, and MRD-negative CR of 55% and 63%, respectively. 31,32 However, it is unclear at this time whether the morbidity associated with such intensive therapies is justified for SMM.…”
Section: Discussionmentioning
confidence: 99%
“…Grade 3-4 toxicities included neutropenia (16%) and infections (12%), mainly related to lenalidomide. Again, single-agent elotuzumab did not show any clinical activity when in the setting of SMM [79].…”
Section: Clinical Developmentmentioning
confidence: 84%
“…69 Elotuzumab was first approved for MM on November 30, 2015. 70 Although no studies have found benefit for elotuzumab monotherapy, either in the advanced 71 or smoldering 72 settings, it has demonstrated significant activity in combination with IMiDs and other agents in the relapsed and refractory setting. 73 At the time of publication, elotuzumab has received FDA approval as combination therapy with lenalidomide and dexamethasone (E-Rd) for the treatment of adult patients with RRMM who have received one to three prior therapies or in combination with pomalidomide and dexamethasone (E-Pd) for adult patients who have received at least two prior therapies including lenalidomide and a PI.…”
Section: Special Considerationsmentioning
confidence: 99%